The effectiveness of trimetazidine and fabomotizole in the prevention of angina progression and improvement of life quality in patients in area of armed conflict - Z. Yu. Shakhbiyeva; A. A. Abdullaev; U. A. Isiamova; D. D. Abdulpatakhov; A. A. Abdullaeva (Российский кардиологический журнал, 2019)
Aim. To assess the effectiveness of trimetazidine and fabomotizole adding to standard treatment in prevention of stable angina progression and improving of quality of life (QOL) in patients in area of armed conflict.Material and methods. One hundred and twelve patients with stable angina of II-III functional class (FC) living in the area of armed conflict in Chechen Republic. All participants were randomized into two groups. Within 6 months 54 patients from control group used standard therapy (isosorbide dinitrate 40 mg/day, metoprolol tartrate 50-100 mg/day, acetylsalicylic acid 100 mg/day, simvastatin 40 mg/day). In the study group 58 patients additionally took trimetazidine 70 mg/day and fabomotizole 30 mg/day. We used Seattle Angina Questionnaire initially and after 6 months of treatment to determine QOL: frequency of angina attacks, nitroglycerin taking per week and adverse events were evaluated.Results. The frequency of angina attacks and nitroglycerin taking in patients of study group significantly decreased after treatment compared with control group (p<0,05). In the study group, as a result of treatment, there was a statistically significant increase in QOL compared with their initial values. In the control group there was a positive trend in following questionnaire scales: physical activity (p<0,01), angina frequency (p<0,001) and disease perception (p<0,05). According to scales of treatment satisfaction, physical limitation and disease perception, improvement of QOL in the study group were statistically significant comparing with control group (p=0,01; p<0,01 and p<0,01, respectively).Conclusion. In the control group, there is a positive dynamics of QOL parameters on physical activity (p<0,01), frequency of angina attacks (p<0,001) and disease perception (p<0,05) scales. The inclusion of trimetazidine and fabomotizole to the standard treatment carries statistically significant improvement of treatment satisfaction, physical limitation and disease perception scales. The frequency of angina attacks and nitroglycerin taking in patients of study group significantly decreased after treatment compared with control group (p<0,05).